RANCANG BANGUN MESIN PENGADUK ADONAN BAHAN DODOL BATANG DAN BUAH PEPAYA UNTUK MENINGKATKAN KAPASITAS PRODUKSI INDUSTRI KECIL DI PEDESAAN - tiwan, Tiwan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
This  community  service  activity  of  appropriate  technology  based leading program aims to support solving the problem faced by small home industries   KUB   "DHARMA   MAKMUR"   in   the   stirring   process   of homogenizing delicacy dough substance of papaya stem and fruit. This stirring process is the beginning activity of the production process of the papaya stem and fruit delicacy. To solve the problem faced by the working partner, this appropriate technology based community service program focuses on the stirring machine construction  followed  by  the  training  activity  using  the  methods  of:  (1) designing the machine compromised to the working partner needs, (2) lecture of machine working principles, (2) demonstration of the machine operation training, (3) field practice to equip the skills for the members of the home industry of KUB "DHARMA MAKMUR". The product of this community service activity is the realization of a mixing machine unit to stir delicacy dough of papaya stem and fruit having the specifications of: (1) dimension of length x width x height=60x50x80 cm, and (2) electric motor of 0,5 HP. The machine operation technique and safety are conducted by turning the machine on until the normal speed of the stirring plate rotation and adjusting the stirring plate rotation speed considering the delicacy dough being mixed. The productivity of the machine produced by this appropriate technology based community service leading program can be eight to ten times quicker compared to working with manual equipments.